2022
DOI: 10.15581/003.35.3.33-49
|View full text |Cite
|
Sign up to set email alerts
|

Political advertising on social media: Issues sponsored on Facebook ads during the 2019 General Elections in Spain

Abstract: Facebook’s advertising platform provides political parties with an electoral tool that enables them to reach an extremely detailed audience. Unlike television, the sponsored content on Facebook is seen only by the targeted users. This opacity was an obstacle to political communications research until Facebook released advertiser-sponsored content in 2018. The company’s new transparent policy included sharing metadata related to the cost and number of impressions the ads received. This research studies the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The combination of experience sampling and tracking data may offer a way forward when (a) aiming for a complete and general picture of a recipient’s mobile communication environment and (b) describing detailed insights into the reactions and usage of mobile communication (Beraldo et al, 2021). As this study has demonstrated, browser tracking can be used as a benchmark for the quality of data obtained through MESM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of experience sampling and tracking data may offer a way forward when (a) aiming for a complete and general picture of a recipient’s mobile communication environment and (b) describing detailed insights into the reactions and usage of mobile communication (Beraldo et al, 2021). As this study has demonstrated, browser tracking can be used as a benchmark for the quality of data obtained through MESM.…”
Section: Discussionmentioning
confidence: 99%
“…While MESM designs alone are already well-suited to facing some of the challenges described above, such as mobile communication exposure and dynamics, it is a valuable approach to combine the intensive longitudinal data with other data sources such as tracking data or data donations (Beraldo et al, 2021). In our example, participants used the screenshot function of their mobile devices to provide the researcher with information on the content of a political ad that they received.…”
Section: Mobile Devices As Tools For Mobile Communication Researchmentioning
confidence: 99%
“…Manual labeling of large amounts of ads is time-consuming and costly, a few recent works have proposed methods to automatically label ads. Baviera et al [9] used the Key-phrase Digger algorithm [38] to detect the main terms in the texts of the 14 684 Facebook ads. They found that the main aim of the ads was to mobilize voters.…”
Section: Related Workmentioning
confidence: 99%
“…The two thirds of online news receivers use -consciously or not -algorithms which have been adequately designed by those who manage particular Internet platforms in order to provide marketing contents and information contents through the designed communication channels. Considering the quality of information, receivers of such media are led to the siloes or filter bubbles and they become susceptible to the impact of disinformation and fake news (Baviera, Sánchez-Junqueras, & Rosso, 2022). C.R.…”
mentioning
confidence: 99%